2008 2nd International Symposium on Systems and Control in Aerospace and Astronautics 2008
DOI: 10.1109/isscaa.2008.4776288
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation for aerodynamic heating and opposing jet thermal protection

Abstract: Based on the theory and semi-em pirical form ulas, the surface heating flux of warhead at zero attack angle under aerodynamic heating is calculated by using reference enthalpy method, and the equilibrium curves of temperature for radiation of wall are obtained, by which the anti-thermal effects of blunt leading edge is proved in this paper. At the same time, the anti-thermal effects of thermal protection system with opposing jet are simulated by using methods of CFD. The heating flux of wall under opposing jet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Meyers et al [144] showed that both skin friction drag and aeroheating reduction were correlated to larger jet size. Eventually, the overall drag and aeroheating on the vehicle are reduced [145,146].…”
Section: Principle Of Operation Of Counterflow Jetsmentioning
confidence: 99%
“…Meyers et al [144] showed that both skin friction drag and aeroheating reduction were correlated to larger jet size. Eventually, the overall drag and aeroheating on the vehicle are reduced [145,146].…”
Section: Principle Of Operation Of Counterflow Jetsmentioning
confidence: 99%
“…Surface Heat Flux Calculation. The heat flux estimated accurately is a prerequisite for the above work, this paper uses numerical calculation combined with engineering calculation [3,4,5] to solve the Euler equations for the external inviscid flow field, thus the outer parameters of boundary layer are determined, then the Surface heat flux is calculated by the engineering method.…”
Section: Aerodynamic Heating Estimationmentioning
confidence: 99%
“…The Fay-Riddell formula [6,7,8] is chosen to calculate the surface heat flux. Assume relevant non-dimensional parameters are constant: Pr = 0.71, Le = 1.0 2.0 ∼ , = 0.17…”
Section: Aerodynamic Heating Estimationmentioning
confidence: 99%
“…In recent years, China has gradually begun to study the problem of drag reduction and heat reduction of high-speed aircraft. Wang et al numerically studied the thermal protection of the jet flow and analyzed the influence of the flow control parameters on the drag reduction and heat reduction effect of the jet flow [14][15][16]. Zhao and Jiang studied the experimental study and numerical simulation of the drag reduction mechanism of jet ions [17] and discussed the effects of plasma energy, ignition position, and shape on the drag reduction performance.…”
Section: Introductionmentioning
confidence: 99%